Central nervous system infection caused by Mycobacterium houstonense: A case report - Wang, LiXia; Wang, FaPing; Yang, Chuan; Luo, FengMing (Frontiers in Neurology, 2022)
Background Mycobacterium houstonense is a rapidly growing mycobacterium (RGM) that belongs to the unnamed third biovariant complex of the Mycobacterium fortuitum group, which is rarely responsible for human infection. Approximately 76% of infections caused by the M. fortuitum group occur after open fractures or skin, soft tissue, bone, or puncture wounds. To date, only a few cases of human infectious disease caused by M. houstonense have been reported worldwide. Case presentation We present a case of a 26-year-old man with a central nervous system (CNS) infection caused by M. houstonense. The patient was transferred to our hospital because of headaches and muscle strength changes. One month prior to presentation at our hospital, the patient was diagnosed with tuberculous meningitis at the other two hospitals, but his condition did not improve after anti-tuberculous treatment, antibiotics, and anti-viral treatment before admission to our hospital. Lumbar puncture was performed at both previous hospitals, as well as at our hospital; the results consistently indicated high cerebrospinal fluid (CSF) opening pressure. M. houstonense was detected in the CSF of the second hospital's lumbar puncture by metagenomic next-generation sequencing (mNGS) but was not identified at our hospital. The patient was discharged from our hospital after receiving non-tuberculous mycobacterium (NTM) treatment for 1 month according to the Chinese NTM guidelines. However, the patient died 20 days after discharge. Conclusion Since it is difficult to identify M. houstonense, this is the first case of human CNS infection caused by M. houstonense in China. This case may be considered by neurologists and infectious physicians when CNS infection does not respond to conventional treatment, especially in the uncommon type of NTM.